The Labor Market and Poverty in Sudan - Etang Ndip, Alvin; Lange, Simon (World Bank, Washington, DC, 2021)
Using the most recent household survey data, this paper examines the characteristics of Sudan’s labor market as it relates to poverty outcomes. Several important aspects of the labor market are analyzed, including the relationship between labor market indicators and the demographic structure of the population, geographic location, education, and gender. It highlights the significant differences in labor market outcomes depending on the structure and distribution of the population and Sudan’s labor market’s many challenges across different dimensions, including demography, gender, and geography. The four key messages can be summarized as follows: first, Sudan is at the verge of entering the earl-dividend stage of the demographic transition. Sudan’s population, while still very young, is on track to enter into the early-dividend stage of the demographic transition within just a few years, raising the stakes for job creation and investment in human capita. Second, while we find evidence for an increase in employment and labor force participation at the national level, this increase seems to be driven by seasonal labor in agriculture and increasing economic hardship, respectively. In urban areas, however, unemployment increased sharply, especially among youth. And despite the overall increase in employment and labor force participation, Sudan’s labor market still underperforms in comparison to its peers. Third, Sudan’s labor market is characterized by large gender disparities, including in terms of employment opportunities and pay. Finally, we find no signs of the beginnings of a structural transformation over the time-period author study; agriculture remains the mainstay of a large majority of employed Sudanese. Rather, labor productivity and real wages outside of agriculture declined markedly between 2009 and 2014, especially in sectors with links to the oil economy. The paper offers policy insights to enhance the role of the labor market in reducing poverty and boosting shared prosperity in Sudan, key among which are 1) encouraging private sector growth, 2) overcoming gender discrimination in the labor market, 3) investing in agriculture and re-storing price incentives, and 4) further expanding access to quality education.